2018
DOI: 10.1021/acs.jchemed.7b00941
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Time-Resolved Spectroscopy: Nanosecond Transient Absorption and Time-Resolved Fluorescence of Eosin B

Abstract: Here we present a new undergraduate laboratory that will introduce the concepts of time-resolved spectroscopy and provide insight into the natural time scales on which chemical dynamics occur through direct measurement. A quantitative treatment of the acquired data will provide a deeper understanding of the role of quantum mechanics and various phenomenological expressions in predicting kinetic rates for fluorescence, phosphorescence, and nonradiative decay mechanisms. This laboratory framework focuses specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…[75] Thed etection of highly elusive intermediates,i ncluding non-radical ones,r equires more sensitive time-resolved spectroscopic techniques, [76] such as laser flash photolysis (LFP). [77] These methods enable the observation of species with lifespans in the order of pico/femto-seconds,i ncluding molecules in their triplet/singlet excited states and transient ionic radicals.I nL FP,a na nalyte mixture is exposed to intermitting irradiation by an ultrafast pulsing laser. The difference in absorbance or emission before and after light collision (the optical deviation, DOD) is recorded.…”
Section: Detection Of Reaction Intermediatesmentioning
confidence: 99%
“…[75] Thed etection of highly elusive intermediates,i ncluding non-radical ones,r equires more sensitive time-resolved spectroscopic techniques, [76] such as laser flash photolysis (LFP). [77] These methods enable the observation of species with lifespans in the order of pico/femto-seconds,i ncluding molecules in their triplet/singlet excited states and transient ionic radicals.I nL FP,a na nalyte mixture is exposed to intermitting irradiation by an ultrafast pulsing laser. The difference in absorbance or emission before and after light collision (the optical deviation, DOD) is recorded.…”
Section: Detection Of Reaction Intermediatesmentioning
confidence: 99%
“… Overview of time scales of molecular motions. The contents of this figure were excerpted from the contents of the study mentioned in [ 8 , 9 , 10 ]. …”
Section: Figurementioning
confidence: 99%
“…In order to observe the dynamics of a molecule, it is important to understand the time scale of the motion of the target molecule ( Figure 1 ). The time scales of molecular motion such as electronic motion, photodissociation, photoionization, bond vibrations, molecular collisions, vibration relaxation, solvation, proton transfer, temperature jump Raman, fluorescence, molecular rotations, large molecule relaxation, molecular diffusion, and phosphorescence motion varies between a few seconds to femtoseconds [ 8 , 9 , 10 ]. When observing the dynamics of a molecule, the movement time scale of the molecule must be considered and an appropriate experimental technique must be applied to observe it.…”
mentioning
confidence: 99%
“…The high prices and toxicity of organometallic complexes has led researchers to explore more environmentally friendly and inexpensive options such as organic dyes, which are organic molecules that absorb in the visible light spectrum and also display long-lived triplet states with redox properties ( Figure 6). [96][97][98][99][100][101] In 2016, Luo et al reported the first example of the direct C-H phosphorylation of thiazoles photocatalyzed by an organic dye, Eosin B (Scheme 24). 102 Radical-scavenger experiments suggest the mechanism to be radical, and the tentative mechanism proposed by the authors follows the direct oxidation of the trivalent tautomer form of diphenylphosphine oxide by the excited Eosin B to give a P radical.…”
Section: Organic Dyes As Catalystsmentioning
confidence: 99%